Reading Comprehension of Various Infographics… in the Field of Nature by Young People with Hearing Impairment - Zielińska, Jolanta (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The aim of the research presented in the paper was to determine the effectiveness of reading short scientific and informational content on various forms of infographics, taken from the school textbook for teaching nature. The study covered 48 students aged 16 (24 students with hearing impairment and 24 non-disabled students). The research results were prepared in two forms: graphical (heat maps, scan paths) and numerical. The conducted research showed that hearing youth prefer presentation of information in textbooks in the form of diagrams described by text (in many textbooks such infographic representation of information is used). However, for deaf youth, a much better solution is to present information through a separate text and its representation in the form of illustrations.